BURKITT’S LYMPHOMA WITH A PRIMARY LESION OF THE STOMACH (CLINICAL OBSERVATION) - A. O. Kasimova; Yu. D. Udalov; V. V. Korenkov; L. Yu. Ilchenko (Архивъ внутренней медицины)
The article describes the case of the primary stomach lymphoma of the stomach in a 29-year-old man. The literature data on the etiology, diagnosis and morphological characteristics of the primary lymphomas of the stomach are presented, the questions of treatment tactics, variants of cytostatic therapy schemes are touched upon.In the described clinical example, the patient’s medical history is given: from the age of 16 the chronic gastroduodenitis is diagnosed, the patient periodically took omeprazole with a positive effect, there is no evidence of infection with Hp and there is no eradication. In April 2016, he noted the deterioration of health in the form of the appearance of discomfort in the epigastric region. In April 2016, an EHDS was performed at the outpatient stage, where an antral tumor of the stomach was detected, and a biopsy of the formation was taken. Histological examination of atypical cells was not revealed, and in connection with this, in May 2016, he was hospitalized at the A.M. Burnazyan for additional examination.The article presents  data  of laboratory  and instrumental examination,  the  results  of EGDS, CT of thoracic  and abdominal  cavities, cytological, immunohistochemical,  and cytogenetic studies.The patient  was given three courses of cytostatic  therapy. The first course of cytostatic  therapy was started  in June 2016, the patient  transferred it satisfactorily, in the post-cytostatic period there was a leukopenia of 2,5 thousand  cells/μl, against which the viral lesion of the tongue mucosa developed, and the therapy with virolex was performed with positive dynamics.The EGD control showed marked positive dynamics. The second and third courses were conducted in July-August 2016, treatment was satisfactory. In September 2016 he was discharged for dynamic observation by a hematologist.The article draws the attention of medical practitioners  to the fact that, in the absence of specific clinical manifestations, the basis for the diagnosis of lymphoma in this clinical example is the timely conduct of an endoscopic study with histological, immunohistochemical and cytogenetic  study of the biopsy.